Picaduras en humanos por una avispa parasitoide del género Sclerodermus (Hymenoptera: Bethylidae) en Venezuela: Stings in humans by a parasitoid wasp of the genus Sclerodermus (Hymenoptera: Bethylidae) in Venezuela - Brewer-Carías, Charles; Brewer, Karen; González, Jorge M. (Anartia, 2021)
Wasps of the family Bethylidae are very diverse, with over 2,920 described species. They range from small to medium-sized, are frequently dark-colored and commonly known as flat wasps (Azevedo et al. 2018, Colombo et al.2020). The females of many bethylids are ant-like in ap-pearance, frequently apterous, but some species are poly-morphic and females could be both apterous and macrop-terous (Richards 1939, Evans 1964, 1978, Colombo & Azevedo 2020). Flat wasps parasitize larvae of Lepidop-tera and Coleoptera and few species have been reported to sting humans, causing slight to severe pain and allergic reactions to those who suffered the wasp attack (Oda et al.1981, Harris 1996, Lee et al. 2014, Papini 2014, Almeida 2017, Skvarla 2018). Wasps in this family, like many other wasps, have the property of inoculating an anesthetic that paralyzes their host, which is later taken as food for the wasp’s offspring (González & Terán 1996, Matthews et al.2009, Lee et al. 2014, Almeida 2017).